2008
DOI: 10.5194/acpd-8-9883-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement of black carbon at Syowa station, Antarctica: seasonal variation, transport processes and pathways

Abstract: Abstract. Measurement of black carbon (BC) was carried out at Syowa station Antarctica (69° S, 39° E) from February 2004 until January 2007. The BC concentration at Syowa ranged from below detection to 176 ng m−3 during the measurements. Higher BC concentrations were observed mostly under strong wind (blizzard) conditions due to the approach of a cyclone and blocking event. The BC-rich air masses traveled from the lower troposphere of the Atlantic and Indian Oceans to Syowa (Antarctic coast). During the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 51 publications
(81 reference statements)
7
35
1
Order By: Relevance
“…The mass attenuation coefficient of Aethalometer AE-16 was 16.8 m 2 g −1 . Junker et al (2006) indicated that thermo-optical method suggested a much higher value (35 m 2 g −1 ) in clean marine sector samples, which would result in an even lower threshold BC value of 24 ng m −3 and the typical clean marine sector values of only 5-10 ng m −3 , which would then be comparable to BC values from the pristine environments (Hansen et al, 1988;Hara et al, 2008;Sciare et al, 2009;Shank et al, 2012). In summary it suggests that EBC values reported for MH (Mace Head) are most likely systematically biased high.…”
Section: Aerosol Characterisation Under Wind-sector Controlled Samplingmentioning
confidence: 85%
“…The mass attenuation coefficient of Aethalometer AE-16 was 16.8 m 2 g −1 . Junker et al (2006) indicated that thermo-optical method suggested a much higher value (35 m 2 g −1 ) in clean marine sector samples, which would result in an even lower threshold BC value of 24 ng m −3 and the typical clean marine sector values of only 5-10 ng m −3 , which would then be comparable to BC values from the pristine environments (Hansen et al, 1988;Hara et al, 2008;Sciare et al, 2009;Shank et al, 2012). In summary it suggests that EBC values reported for MH (Mace Head) are most likely systematically biased high.…”
Section: Aerosol Characterisation Under Wind-sector Controlled Samplingmentioning
confidence: 85%
“…This evidence can mean that nitrate sources (especially stratosphere-troposphere transport and re-emission of NO x from the snow surface) are more intense in this season. In addition, we have to note that meridional transport of nitrate and sulfate from lower latitudes is more efficient in summer, due to the weakening of the polar vortex (Hara et al, 2008). Finally, higher temperature and intense solar irradiation make more efficient the photochemical oxidation of NO x and SO 2 to nitric and sulfuric acid.…”
Section: Ion Balancementioning
confidence: 99%
“…Even a small quantity of absorbing aerosols (anthropogenic or natural) over the highly reflecting snow might enhance the warming of the atmosphere (Chylek and Coakley, 1974;Randles et al, 2004) and the deposition of these particles over the surface of the snow or ice reduces the albedo (Russell et al, 2002;Hansen and Nazarenko, 2004). As such, there is an increased interest and need to investigate the properties of Antarctic aerosols, and their spatial temporal and microphysical properties to understand their climate forcing potential (Valero et al, 1983;Herber et al, 1993;Schwartz and Andreae, 1996;Hatzianastassiou et al, 2004;IPCC, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These include atmospheric particles as well (Shaw, 1979;Tomasi et al, 2007;Weller et al, 2008;Chaubey et al, 2010). Antarctic aerosols comprise of mainly sea salt, sulphate, dust, nss sulphate, NH + 4 , NO − 3 , Methane Sulphonate Niemi et al, 2005;Virkkula et al, 2006;Tomasi et al, 2007) and a small amount of efficient absorbing aerosols like black carbon (Bodhaine, 1995;Hansen et al, 2001;Hara et al, 2008;Chaubey et al, 2010). Even a small quantity of absorbing aerosols (anthropogenic or natural) over the highly reflecting snow might enhance the warming of the atmosphere (Chylek and Coakley, 1974;Randles et al, 2004) and the deposition of these particles over the surface of the snow or ice reduces the albedo (Russell et al, 2002;Hansen and Nazarenko, 2004).…”
Section: Introductionmentioning
confidence: 99%